Evaluation of The Financial Performance of The People's Credit Bank Owned By The West Java Provincial Government In 2020-2022 - Didit Supriyadi; Muhammad Irfan Dipradja; Evi Selvi (Dinasti Publisher, 2025)
The West Java Provincial Government in improving the regional economy has formed Regionally Owned Enterprises (BUMD). One of them is the People's Credit Bank (BPR). As civil servants who have the task and function to foster BUMD, it is supposed to evaluate BPR owned by the Regional Government of West Java Province to measure the performance of BPR and whether BPR contributes to regional revenue. The purpose of writing this paper is to analyze BPR's financial statements over the past three years and see the development of the company's performance and its benefits to shareholders, in this case the West Java Provincial Government in the form of dividends. In conducting evaluation, horizontal analysis is used to describe trends or movements of important posts in the financial statements and uses vertical analysis to see the proportion of the headings of the financial statements.